2018
DOI: 10.1190/geo2017-0248.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic resolution enhancement using scale transform in the time-frequency domain

Abstract: Reducing uncertainty in geologic interpretation of petroleum reservoir containing thin layers requires increasing vertical resolution via appropriate advanced resolution enhancement methods. This problem was resolved here by introducing an alternative approach in resolution enhancement. Our method uses Gabor deconvolution (GD) combined with wavelet scaling. First, the seismic trace is transformed in the time-frequency domain using the Gabor transform. Subsequently, the Gabor magnitude spectrum of the seismic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A variety of VRE methods and strategies are available to solve the problem of thin-layer interpretation in seismic data [38]. Alaei et al [39] proposed a novel strategy of nonstationary scale transformation filter for VRE. The application of this method to three seismic data sets showed that it not only increases the bandwidth frequency of the data but it also increases the dominant frequency of bandwidth compared with the Gabor deconvolution method.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of VRE methods and strategies are available to solve the problem of thin-layer interpretation in seismic data [38]. Alaei et al [39] proposed a novel strategy of nonstationary scale transformation filter for VRE. The application of this method to three seismic data sets showed that it not only increases the bandwidth frequency of the data but it also increases the dominant frequency of bandwidth compared with the Gabor deconvolution method.…”
Section: Discussionmentioning
confidence: 99%
“…Although many linear approximation equations have been proposed, in order to improve the accuracy of reservoir fluid prediction, the high-order approximate scattering coefficient equation is derived using the medium decomposition theory. Through analysis, Aki and Richards (2002) gave the expression of scattering matrix in the case of plane wave incident as…”
Section: Quadratic Scattering Coefficientmentioning
confidence: 99%
“…Based on the exact Zoeppritz equations (Zoeppritz, 1919), AVO technology can predict reservoir parameters using the Bayesian estimation (Li et al, 2020;Wilson et al, 2009). Due to the complex structure of the exact Zoeppritz equations, it is difficult to apply them directly (Aki & Richards, 2002;Lan & Zong, 2022;Shuey, 1985). As a result, numerous researchers have attempted to simplify and approximate the Zoeppritz equation in diverse ways to tackle this challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic data reconstruction is important in seismic imaging. Many traditional intelligent methods have been proposed to solve various problems in seismic imaging, such as seismic resolution enhancement (Alaei et al, 2018;Soleimani, 2016;Soleimani, 2017;Soleimani et al, 2018;Mahdavi et al, 2021), complex geological structure identification (Soleimani, 2015;Farrokhnia et al, 2018;Kahoo et al, 2021;Khasraji et al, 2021;Hosseini-Fard et al, 2022;Khayer et al, 2022a;Khayer et al, 2022b), and noise attenuation (Gholtashi et al, 2015;Siahsar et al, 2017;Anvari et al, 2018;Anvari et al, 2020). In recent years, deep learning has achieved outstanding successes in a variety of domains, including computer vision (Ferdian et al, 2020;Manor and Geva, 2015) and medical image processing (Li et al, 2021;Tavoosi et al, 2021), with its powerful representing ability.…”
Section: Introductionmentioning
confidence: 99%